(untitled) (Journal of Dhaka Medical College, 2015)
Castlemans disease is a rare lymphoproliferative disorder. Castlemans disease is a disease which involves massive non-malignant proliferation of lymphoid tissues that usually presents as mediastinal masses as well as other groups of lymphnodes. That is why, sometimes, confusion may arise whether the lymphadenopathy is benign or malignant. However, some authors describes, histologically and prognostically Castlemans disease is distinct from malignant lymph-node hyperplasia. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22707 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 124-127